The Effect of Online Game Streaming on Tiktok Accounts @Serveretherblade on the Level of Audience Satisfaction - M Rifkhan Alfaruqy (Lenggogeni Data Publishing, 2024)
The Tiktok account @serveretherblade with 1,990 followers is one of those who stream online games through the Tik Tok application. A broadcast can produce an impact that is felt directly by the audience. Like the followers of the @serveretherblade tiktok account who watch streaming online games, of course, through the information conveyed, they also have entertainment to fill their free time by watching streaming shows on the account. This study aims to determine the level of satisfaction of the audience of the @serveretherblade tiktok account. Research using explanatory quantitative. The data collection method used was a Google Form questionnaire using a Likert Scale and literature review. This study uses non-probability sampling with the sample collection technique is convenience sampling. Data analysis using SPSS. Respondents in this study were 100 followers of the Tiktok @serveretherblade account. The validity test resulted in an r-table value of 0.196. The results of SPSS data processing show that r-count> r-table, so the 12 statement instruments are declared valid. The reliability test shows the Cronbach's alpha value of the variables tested is above 0.6. So it proves to be reliable. The conclusion of this study is the results of the hypothesis obtained, t count> t table. Thus it is rejected, meaning that there is a positive and significant influence between